RAPNO efforts in Brain Tumour Outcomes - Qurat-ul-Ain Virani; Zanib Javed; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2024)
Assessing treatment efficacy for brain tumours has evolved since its inception with the introduction of MacDonald’s criteria, which pioneered the utility of imaging to determine an objective and quantifiable response to treatment. This criterion failed to distinguish pseudo response or progression from progression and did not account for non-enhancing disease therefore; the response assessment in neuro-oncology (RANO) working group was established to account for these limitations. Since, its commencement it has worked to determine response assessment for multiple tumours. As paediatric tumours exhibit heterogeneous and variable-enhancing characteristics, the response assessment in paediatric neuro-oncology (RAPNO) working group was formed to create separate criteria. Six response criteria have been published to date, and the article summarizes them. Keywords: RAPNO, neuro-oncology, response assessment